Using Science, Technology, Society, and Environment (STSE) Approach to Improve the Scientific Literacy of Grade 11 Students in Plant Growth and Development - Kultida Chanapimuk; Sureeporn Sawangmek; Pranee Nangngam (Journal of Science Learning, 2018)
The environmental issues surrounding agrochemical products facing people today include serious health and ecological problems.  Scientific literacy is necessary for students to understand scientific knowledge and get ready for the future world.  Therefore, this action research aims to promote scientific literacy, in the area of plant growth by using the Science, Technology, Society and Environment (STSE) approach that consists of 4 steps: 1) motivation; 2) exploration; 3) brainstorming; and 4) decision making.  The participants are 35 special program students in grade 11. The PISA-like test and worksheets were used to collect data.  Content analysis and triangulation were used to indicate the development of scientific literacy.  The findings show that the students have better scientific literacy and higher competencies in explaining phenomena scientifically, evaluating and designing scientific inquiry and interpreting data and evidence scientifically.  This study suggests that student collaboration is essential to improve the scientific literacy of students.